USE OF MODIFIED SCHAFFER’S METHOD FOR THE DETORSION OF UTERUS IN A PLURIPAROUS EWE - TEJA, A; SHANMUKHI, S; HEMKUMAR, B; MOULI KRISHNA4, K (The Indian Journal of Animal Reproduction, 2016)
Pervaginal examination in pluriparous ewe with the history of dystocia was carried out using a vaginal speculum. The twisting of vagina in clockwise fashion was revealed, however, the cervix was not visible. Schaffer’s method of detorsion using a plank was adopted with a few modifications. The lambing was successful after rolling the ewe on its right side.